Perspectives on setting limits for RF contact currents: a commentary - Tell, Richard A.; Tell, Christopher A. (Biomedical engineering online, 2018)
Limits for exposure to radiofrequency (RF) contact currents are specified in the two dominant RF safety standards and guidelines developed by the Institute of Electrical and Electronics Engineers (IEEE) and the International Commission on Non-Ionizing Radiation Protection (ICNIRP). These limits are intended to prevent RF burns when contacting RF energized objects caused by high local tissue current densities. We explain what contact currents are and review some history of the relevant limits with an emphasis on so-called "touch" contacts, i.e., contact between a person and a contact current source during touch via a very small contact area. Contact current limits were originally set on the basis of controlling the specific absorption rate resulting from the current flowing through regions of small conductive cross section within the body, such as the wrist or ankle. More recently, contact currents have been based on thresholds of perceived heating. In the latest standard from the IEEE developed for NATO, contact currents have been based on two research studies in which thresholds for perception of thermal warmth or thermal pain have been measured. Importantly, these studies maximized conductive contact between the subject and the contact current source. This factor was found to dominate the response to heating wherein high resistance contact, such as from dry skin, can result in local heating many times that from a highly conductive contact. Other factors such as electrode size and shape, frequency of the current and the physical force associated with contact are found to introduce uncertainty in threshold values when comparing data across multiple studies. Relying on studies in which the contact current is minimized for a given threshold does not result in conservative protection limits. Future efforts to develop limits on contact currents should include consideration of (1) the basis for the limits (perception, pain, tissue damage); (2) understanding of the practical conditions of real world exposure for contact currents such as contact resistance, size and shape of the contact electrode and applied force at the point of contact; (3) consistency of how contact currents are applied in research studies across different researchers; (4) effects of frequency.